Distribution of banana Fusarium wilt in Banyumas, Indonesia, and characterization of F. oxysporum isolates from infected bananas and taro growing on the same farm - RUTH FETI RAHAYUNIATI; RULY EKO KUSUMA KURNIAWAN; ENDANG MUGIASTUTI (Society for Indonesian Biodiversity, 2024)
Abstract. Rahayuniati RF, Kurniawan REK, Mugiastuti E. 2024. Distribution of banana Fusarium wilt in Banyumas, Indonesia, and characterization of F. oxysporum isolates from infected bananas and taro growing on the same farm. Biodiversitas 25: 1344-1351. Fusarium wilt disease is a major constraint to banana production in Indonesia. The disease has also affected banana production in Banyumas, one banana-producing region. However, information on the distribution and characteristics of Fusarium wilt in Banyumas is limited. Growing mixed bananas and taro on the same farm in Banyumas is common. During the banana wilt survey, we found that taro also showed a symptom of Fusarium wilt. Therefore, this study aims to determine the distribution of Fusarium wilt disease on bananas in Banyumas, determine the characteristics of F. oxysporum on bananas and taro that grow on the same farm, and conduct pathogenicity tests of taro Fusarium isolates on bananas. The study consists of two steps, i.e., survey and sampling using purposive sampling technique conducted at the banana-growing area in Baturraden, Rawalo, Wangon, Purwojati, Gumelar, Ajibarang, Kemranjen, and Somagede districts. The second step involved the identification, characterization, and pathogenicity test of Fusarium isolate banana compared to isolate taro. A complete randomized design was used in an experimental study. All samples with Fusarium wilt symptoms were identified morphologically as comprised of macroscopic, microscopic characters and volatile odor of isolates. The results indicated that Fusarium wilt was equally distributed in Banyumas District, with the disease incidence reaching 50%. F. oxysporum isolates, which cause Fusarium wilt of banana and taro in Banyumas District, have indicated the same characteristics as Foc, i.e., diverse colony morphology, dominated by white to purple colonies with a cottony, smooth, and dry surface. Colonies are circular, irregular, dispersed, and undispersed on the surface of the medium with a filamentous margin; the single-septate oval-shaped microconidium and typical straight to sickle-shaped macroconidium. There were no significant differences between F. oxysporum isolate banana and taro in terms of disease incubation period, disease intensity, and Area Under Disease Progress Curve (AUDPC). Generally, this study found that Fusarium wilt was equally distributed in the lowlands. The Fusarium in bananas was the same as the Fusarium on taro in the same area, and the Fusarium isolated from taro effectively infected the banana.